The Influence of Knowledge Management and Motivation on Job Satisfaction and Employee Performance in the Population and Civil Registration Office of DKI Jakarta Province - Firman Firman (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to analyze the influence of Knowledge Management (KM) and motivation on employee job satisfaction and performance at the Population and Civil Registration Office of DKI Jakarta Province. The analytical method used is Partial Least Squares (PLS), a statistical approach capable of handling complex structural models with relatively small samples. Data collection method through a survey of 150 employees randomly selected from various work units at the Population and Civil Registration Office of DKI Jakarta Province. Using the Partial Least Squares (PLS) approach to test the relationships between variables, the survey instrument used has been validated and its reliability tested before distribution. The results of the analysis indicate that there is a positive and significant influence of Knowledge Management (KM) on employee motivation. Additionally, motivation also has a positive and significant effect on employee job satisfaction and performance. However, the direct influence of Knowledge Management (KM) on job satisfaction is not significant. The analysis also shows that there is a positive and significant indirect influence of Knowledge Management (KM) on employee performance through motivation. These findings provide practical implications for management at the Population and Civil Registration Office of DKI Jakarta Province in managing Knowledge Management (KM) and motivating employees to enhance their job satisfaction and performance. This study also contributes to the literature in the field of human resource management and Knowledge Management.